(untitled) (Journal of actual problems of jurisprudence, 2019)
The main body of this article is the analysis of a current situation about transparency and accountability in the sphere of state fi nancing in the Republic of Kazakhstan. New methodological approaches, ideas and developments in this sphere are researched. On the basis of foreign experience studying certain recommendations are given. They concern increasing the level of transparency in the sphere of state fi nancing management.